Γ‐d‐Glutamyl‐meso‐diaminopimelic acid induces autophagy in bovine hepatocytes during nucleotide‐binding oligomerization domain 1‐mediated inflammation. Issue 7 (24th December 2020) - Roy, Animesh Chandra; Chang, Guangjun; Roy, Shipra; Ma, Nana; Gao, Qianyun; Shen, Xiangzhen
Abstract: Autophagy is a crucial cellular homeostatic process and an important part of the host defense system. Dysfunction in autophagy enhances tissue susceptibility to infection and multiple diseases. However, the role of nucleotide oligomerization domain 1 (NOD1) in autophagy in bovine hepatocytes is not well known. Therefore, our aim was to study the contribution of NOD1 to autophagy during inflammation in response to a specific ligand γ‐d ‐glutamyl‐ meso ‐diaminopimelic acid (iE‐DAP). To achieve this aim, hepatocytes separated from cows at ∼160 days in milk (DIM) were divided into six groups: the nontreated control (CON) group, the rapamycin‐treated (RAP) group as a positive control, the iE‐DAP‐treated (DAP) group, the 3‐MA‐treated (MA) group, the rapamycin with 3‐MA (RM) group, and the iE‐DAP with 3‐MA (DM) group. iE‐DAP administration significantly increased the mRNA expression of NOD1, ATG16L1, RIPK2, ULK1, AMBRA1, DFCP1, WIPI1, ATG5, ATG7, ATG10, ATG4A, IκBα, NF‐κB, CXCL1, IL‐8, and STAT6 and significantly decreased PIK3C3. The protein expression of NOD1, p‐IκBα, p‐NF‐κB/p‐p65, LC3‐II, ATG5, and beclin 1 were significantly upregulated and that of SQSTM1/p62, p‐mTOR, and FOXA2 were significantly downregulated in response to iE‐DAP. iE‐DAP also induced the formation of LC3‐GFP autophagic puncta in bovine hepatocytes. We also knocked down the NOD1 with siRNA. NOD1 silencing suppressed the autophagy and inflammation‐related genes and proteins. The application of the autophagy inhibitor increased the expression of inflammatory molecules and alleviated autophagy‐associated molecules. Taken together, these findings suggest that NOD1 is a key player for regulating both ATG16L1 and RIPK2‐ULK1 directed autophagy during inflammation in response to iE‐DAP in bovine hepatocytes. Abstract : A schematic model of autophagy regulation by iE‐DAP and 3‐MA treatment.